Solenoidal Micromagnetic Stimulation Enables Activation of Axons With Specific Orientation - Golestanirad, Laleh; Gale, John T.; Manzoor, Nauman F.; Park, Hyun-Joo; Glait, Lyall; Haer, Frederick; Kaltenbach, James A.; Bonmassar, Giorgio (Frontiers in Physiology, 2018)
Electrical stimulation of the central and peripheral nervous systems ─such as deep brain stimulation (DBS), spinal cord stimulation, and epidural cortical stimulation are common therapeutic options increasingly used to treat a large variety of neurological and psychiatric conditions. Despite their remarkable success, there are limitations which if overcome, could enhance outcomes and potentially reduce common side-effects. Micromagnetic stimulation (uMS) was introduced to address some of these limitations. One of the most remarkable properties is that uMS is theoretically capable of activating neurons with specific axonal orientations. Here we used computational electromagnetic models of the uMS coils adjacent to neuronal tissue combined with axon cable models to investigate uMS orientation-specific properties. We found a twenty-fold reduction in the stimulation threshold of the preferred axonal orientation compared to the orthogonal direction. We also studied the directional specificity of uMS coils by recording the responses evoked in the inferior colliculus of rodents when a pulsed magnetic stimulus was applied to the surface of the dorsal cochlear nucleus. The results confirmed that the neuronal responses were highly sensitive to changes in the uMS coil orientation. Accordingly, our results suggest that uMS has the potential of stimulating target nuclei in the brain without affecting the surrounding white matter tracts.